Proyecto de factibilidad para la instalación de una empresa de producción y comercialización de productos personalizados y subliminados en la parroquia Vilcabamba, del cantón Loja, 2022 - Aguilera Gonzalez, Janeth Elizabeth (2023)
This scientific paperwork of investigation aims to determine the feasibility of implementing a production and commercialization company of personalized and sublimated products in the Vilcabamba parish of the Loja canton. The following methods were used: deductive, inductive, analytical, as well as the techniques of surveys and, interviews and research instruments; the chosen segment was the economically active population of the Vilcabamba parish of 3,055 inhabitants from 20 to 64 years of age, and we calculated a sample of 341 surveys, 055 inhabitants from 20 to 64 years of age. And we calculated from a sampling of 341 surveys, detecting an unsatisfied demand of 5,721 cups and 4,041 T-shirts; likewise, we determined an annual supply of 1,519 mugs and 731 T-shirts for the first year. The technical study determined an installed capacity of 23,040 cups and 7,680 T-shirts per year, of which 100% of this capacity; would be used in the cups and similarly in the T-shirts; the company name will be ''SUBLIMATED'' Limited Company. The investment for the execution of this research paperwork; would be about 17,999.11 dollars, which we will finance with 56% of its capital and 44% from external sources (loan). 748.38; IRR of 76.10%; Benefit-cost ratio of 1.19 dollars, which indicates that we will recover for every dollar invested 0.19 cents of profitability, the capital recovery period will be two years and 15 days; the project supports an increase in costs of 10.86% and a 9.31% decrease in income, with this we concluded that the project is feasible.